Integrins in development: moving on, responding to, and sticking to the extracellular matrix. - Bokel, C.; Brown, N.H. (Developmental Cell, 2002)
Integrins are cell surface receptors of the extracellular matrix present in all animals. Genetic analysis in worms, flies, and vertebrates has revealed integrin involvement in key developmental processes, and we focus here on examples of integrin functions that are comparable across these model organisms. Integrins contribute to cell movement by providing traction to migrating cells, through assembly of extracellular matrices that can serve as tracks for migration, and by transmitting guidance signals that direct cells or cell processes to their targets. Integrins also participate in signaling events that govern tissue differentiation and organogenesis. Finally, adhesion by integrin-mediated junctions allows tissues to withstand mechanical load and is essential for tissue integrity.